Expert Answers
sciencesolve eNotes educator| Certified Educator

You should remember that the algorithm you need to follow when you solve the absolute value equation is similar to the algorithm used when solving an absolute value inequality.

You need to set up to cases such that:

`-x +3 gt= 7 or -x + 3lt= -7`

`` Solving the right inequality yields:

`-x + 3 gt= 7 =gt -x gt=-3 + 7 =gt -x gt= 4 =gt xlt= -4`

Solving the left inequality yields:

`-x + 3<= -7 =gt -x<= -3 - 7 =gt -x<= -10 =gt x gt= 10` 

Hence, the solution to the absoute value inequality is: `(-oo, -4]U[10, +oo).`

beckden eNotes educator| Certified Educator

We split the absolute value into two

`-x+3gt=7` or `-x+3lt=-7`

Adding -3 to both sides of both equations

`-xgt=4` or `-xlt=-10`

Multiply both sides by -1 (and reverse the direction of the inequalities) we get

`xlt=-4` or `xgt=10`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question